Understanding children and adolescents - Schickedanz, David I.; Schickedanz, Judith A.; Forsyth, Peggy D.; Forsyth, G. Alfred (Boston : Allyn and Bacon, 2001)
Research, theory, and biology. Infants and toddlers. Preschool children. School-age children. Adolescents.
Keywords: Psychology; Child development; Adolescence; Adolescence; Child development; Child psychology